2007
DOI: 10.1042/bst0351529
|View full text |Cite
|
Sign up to set email alerts
|

Biological consequences of statins in Candida species and possible implications for human health

Abstract: The statins, simvastatin and atorvastatin are the most widely prescribed drugs. Statins lower cholesterol levels through their action on HMG-CoA (3-hydroxy-3-methylglutaryl-CoA) reductase, an essential enzyme for the biosynthesis of cholesterol. Fungal HMG-CoA reductases are also inhibited by statins, resulting in reduced levels of ergosterol (the fungal equivalent of cholesterol) and concomitant growth inhibition. This effect occurs in a range of fungal species and possibly affects fungal colonization of peop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 42 publications
0
19
0
1
Order By: Relevance
“…9, 12, 13 We established that at the concentration of statin and for the period of treatment we employed, petite formation did not occur (Supplementary Fig. 1).…”
Section: Resultsmentioning
confidence: 88%
“…9, 12, 13 We established that at the concentration of statin and for the period of treatment we employed, petite formation did not occur (Supplementary Fig. 1).…”
Section: Resultsmentioning
confidence: 88%
“…In-vitro studies have demonstrated that simvastatin greatly inhibits the growth of Candida species [15,16]. We performed a review to determine if there was a clinical benefit of statin therapy throughout antifungal therapy in intensive care unit patients with confirmed candidemia.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies have demonstrated that simvastatin inhibits the growth of species of Candida spp. and may be useful in the treatment of candidemias 3,7,12 .…”
Section: Introductionmentioning
confidence: 99%